Skill Building for Simple Electrolysis Equipment for Rainwater Treatment in Gemulak, Sayung, Demak, Indonesia - Harianingsih, Harianingsih; Handayani, Sri; Kusumaningrum, Maharani; Sulistyawan, Vera Noviana; Erliana, Savira Rinda; Ubay, Isnina Noor; Pangestu, Indra Sakti (Journal of Community Empowerment, 2024)
Water is essential to human life because it is the main foundation for survival. The service aims to collaborate with Gemulak Sayung Village, Demak Regency, and Jawa Tengah coastal communities to obtain a decent drinking water supply from rainwater treatment using electrolysis science and technology. The stages of service implementation were carried out through observation, training in making simple electrolysis equipment, monitoring, and evaluation. On observation, the problem was obtained: water availability is still minimal for consumption. Implement training in making electrolysis equipment that can be applied in their homes. Monitoring and evaluation are carried out to ensure the sustainability of the service implementation. The service results showed that participants learned about the benefits of rainwater and simple processing technology using electrolysis to produce electrolyzed water in alkaline and acidic water. 95% of participants wanted the service process to be continued because it benefited the Gemulak Village, Sayung, and Demak communities.